UPAYA PENINGKATAN PARTISIPASI MASYARAKAT PADA KEGIATAN POSYANDU LANSIA - Hidayatus Sufyan; Dwi Astuti; Titis Setyandari; Rima Firantika; Anisa Wiwit Oktatrisyani; Annisa Rizka Damayanti; Bayu Anggara Aji; Nuzilul Munawaroh; Anggi Rachma Syahdina; Jenita Berlian Nindyasari; Tanjung Anitasari Indah Kusumaningrum (Universitas Muhammadiyah Surakarta, 2024)
The elderly population in Sukoharjo Regency in 2021 is 21.50% and will increase to 22.16% in 2022. The number of elderly in the Weru District is 11,004 (Central Bureau of Statistics for Sukoharjo Regency, 2022). The number of elderly people in the Ngreco Village based on the 2022 Sukoharjo Population Data is 1251. This community service activity began with conducting a Self-Introspective Survey using the door-to-door method in Gabeng Hamlet, Ngreco Village, with a sample of 151 respondents. Determining the priority of problems in this study using the PAHO (Pan American Health Organization) technique through the Village Community Consultation (MMD). Based on survey data and MMD, the priority problem chosen was the participation of the elderly in Posyandu. Solving the problem was done by intervention through outreach about the importance of joining the elderly's health center, which 134 people attended. Socialization activities aim to get the community to participate in the elderly posyandu regularly, and the results of the socialization show that there is an increase in the knowledge of the elderly about the elderly posyandu from 72.39 to 93.58. The elderly posyandu activities experienced an increase in participants in January 2023 from 13 participants to 72 participants in February 2023. Based on the community service activities that have been carried out, it is recommended that the community participate in the posyandu regularly once a month to carry out health checks to detect illnesses.